LEGAL VALIDITY OF LAND TENURE BY FOREIGNERS THROUGH MIXED MARRIAGES OBTAINED FROM INHERITANCE FROM THE UUPA PERSPECTIVE - I Gusti Made Oka Mahendra; Dewa Gede Pradnyana Yustiawan (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
This scientific paper aims to examine the legal validity of land tenure by foreigners through mixed marriages obtained from inheritance, with a focus on the perspective of the UUPA (Undang-Undang Pokok Agraria). It also investigates the legal consequences that arise from the cancellation of ownership rights to land obtained through inheritance by foreigners. The presence of mixed marriages in Indonesia has implications for joint property ownership in marriage. According to Article 35 of the Marriage Law, joint property refers to assets acquired during marriage that become shared property. However, Article 21, paragraph (3) of the Basic Agrarian Law (Law No. 5/1960) lacks clarity in terms of norms governing land tenure by foreigners derived from inheritance. This ambiguity arises from the absence of a defined time limit or clear provisions regarding land tenure by foreigners through inheritance. This research utilizes normative legal research methods, employing legislative, conceptual, and analytical approaches. Foreign nationals can acquire land ownership if they enter into a mixed marriage with Indonesian citizens. In such cases, the land must remain under the ownership of the Indonesian citizen, with a joint property separation agreement established prior to the mixed marriage. The heirs of foreign nationals can still hold Hak milik land acquired through inheritance, but only for a period of one year. After this period, the land reverts to state ownership. Foreign nationals have the option to sell the land to an Indonesian citizen or apply for a Right of Use through the National Land Agency, in accordance with the applicable regulations.